2002
DOI: 10.1103/physrevlett.89.125506
|View full text |Cite
|
Sign up to set email alerts
|

Density-Fluctuation-Induced Swelling of Polymer Thin Films in Carbon Dioxide

Abstract: We report an anomalous swelling of polymer thin films in carbon dioxide (CO(2)) which is associated (in both locus and form) with the density fluctuation ridge that forms along the extension of the coexistence curve of gas and liquid in the P-T phase diagram. Neutron reflectivity results showed that CO(2) could be sorbed to a large extent ( approximately 60%) in thin polymer films even when the bulk miscibility of the polymer with CO(2) is very poor. The anomalous swelling is found to scale with the polymer ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
123
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(138 citation statements)
references
References 16 publications
14
123
1
Order By: Relevance
“…Near the critical point of CO 2 (31.1 • C and 7.38 MPa), polymer thin films exhibit unique anomalous swelling [26][27][28][29][30], where the density fluctuation of supercritical fluids is believed to induce significant swelling. Koga and coworkers [27][28][29] reported that the anomalous swelling of polymers is strongly correlated with the parameter obtained by dividing the sample thickness by the radius of gyration (R g ), and is clearly observed in films of which the thickness is less than several times of R g . They also recently reported that anomalous swelling can be observed in supercritical methane [29].…”
Section: Introductionmentioning
confidence: 99%
“…Near the critical point of CO 2 (31.1 • C and 7.38 MPa), polymer thin films exhibit unique anomalous swelling [26][27][28][29][30], where the density fluctuation of supercritical fluids is believed to induce significant swelling. Koga and coworkers [27][28][29] reported that the anomalous swelling of polymers is strongly correlated with the parameter obtained by dividing the sample thickness by the radius of gyration (R g ), and is clearly observed in films of which the thickness is less than several times of R g . They also recently reported that anomalous swelling can be observed in supercritical methane [29].…”
Section: Introductionmentioning
confidence: 99%
“…We calculated a linear dilation normal to the surface, S f ¼ (L)L 0 )/L 0 ¼ 0.27 for PS/ gold, where L and L 0 are the measured thicknesses of the exposed and unexposed polymer layers, respectively. This value is much larger than the swelling of the bulk PS (S f ¼ 0.1) [9], but slightly smaller than S f ¼ 0.35 reported for thin films exposed to the P-T values along the ridge [6].…”
Section: Xr Resultsmentioning
confidence: 57%
“…Consequently, as observed in the pure PS films, it is reasonable to say that the surface modification produced by exposure to scCO 2 is a universal phenomenon in filled polymer systems, regardless of the choice of nanoparticles. As summarized in table 1, the inclusion of the nanoparticles tends to suppress the anomalous dilation of the polymeric nanocomposite thin films of thickness 2 R g or less, as compared to the pure exposed PS films [6]. Thus, the coupling of the nanoparticles and polymer thin films immersed in the density fluctuating medium did not show further excess adsorption of scCO 2 molecules into the polymeric nanocomposite thin films.…”
Section: Xr Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Over the past three decades, numerous polymers [1][2][3][4][5][6][7][8] including bulk materials and thin films, either amorphous or semi-crystalline polymers, have been found to be able to dissolve or swell in ScCO 2 with large density fluctuations [9][10][11]. However, very little is clearly known about the interaction between CO 2 and the polymers.…”
Section: Introductionmentioning
confidence: 99%